PELATIHAN MEMBUAT JURNAL UMUM PERUSAHAAN JASA DI SMA TARSISIUS 1 - Alvin T, Theodore Benedict; Syanti Dewi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
In this current era, high school students are certainly required to prepare themselves before entering the field of work they are interested in. With the demands of the present era, students are expected to be able to keep up with development over times and the global development of knowledge. Therefore, SMA Tarisisius 1 offers a variety of extracurricular activities, both academic and non-academic. One of the academic extracurricular activities is accounting. The Faculty of Economics and Business at Universitas Tarumanagara collaborates with several schools, including SMA Tarsisius 1, to help in shaping the mindset of students that accounting is not as difficult as they think and encouraging school to excel in the field of accounting. Training activities are held every Wednesday from 14:30 to 16:00 WIB, attended by one supervising teacher and 15 students from grades 10-12, from various disciplines, both science and social sciences. Students receive modules that cover the general journal material through a PowerPoint presentation. The outcome of implementing the training activity on the process of journalizing service companies at SMA Tarsisius 1 is the increased knowledge and expertise gained by the students regarding service companies. The hope is that through this training, students at SMA Tarsisius 1 can broaden their insights and skills in the field of accounting, preparing them for higher-level studies. The suggestion is to encourage SMA Tarsisius 1 to continue organizing this training activity in the future.